Analisis Pengaruh Struktur Modal Terhadap Kinerja Perusahaan pada Perbankan Syariah di Indonesia - Kelvin Kelvin; Hery Haryanto (ITB AAS INDONESIA Surakarta, 2023)
This study aims to examine the relationship between capital structure as measured by leverage and control variables, namely firm size, firm age, firm growth, tangibility and liquidity on company performance at Islamic commercial banks in Indonesia registered with the Financial Services Authority in the 2012-2021 period. Data were analyzed using descriptive statistics, panel regression analysis, t test, F test, and coefficient of determination and the results showed that there was a significant influence on leverage, company growth, and liquidity on the performance of Islamic banking companies. While other variables, firm size, firm age, and tangibility have no significant effect on the performance of Islamic banking companies in Indonesia.